Indeks nilai penting dan strategi pengelolaan mangrove di Wilayah Pesisir Kabupaten Boalemo - Antu, Yulinda R.; Erlansyah, Erlansyah (Universitas Halu Oleo, 2024)
This research aims to determine mangrove ecosystem management strategies in coastal areas. Data analysis is used for mangrove management strategies in Boalemo Regency, namely AHP analysis. The types of mangroves found in Boalemo Regency are 11 types of mangroves, namely Rhizopora mucronata, Rhizopora apiculata, Rhizopora stylosa, Sonneratia alba, Sonneratia casseolaris, Ceriops decandra, Ceriops Tagal, Avicennia Lanata, Xylocarpus granatum, Excoecaria agalocha, Brugiera Gymnoriza with the highest INP value for the category Seedlings and trees are of the Rizophora mucronata type and the sapling category is of the Ceriops tagal type. The main priority for mangrove ecosystem management in the coastal areas of Boalemo Regency is rehabilitation and conservation, then institutional strengthening as well as training and counseling.